2019
DOI: 10.1159/000503228
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms of Fetal Right Ventricular Fractional Area Change by 2D Echocardiography

Abstract: Objectives: Fetal right ventricular (RV) function assessment is challenging due to the RV geometry and limitations of in utero assessment. Postnatally, 2D echocardiographic RV fractional area change (FAC) is used to assess RV global systolic function by calculating the percentage of change in RV area from systole to diastole. Reports on FAC are scarce in prenatal life, and nomograms throughout pregnancy are not available. Our aims were (1) to study prenatal RV FAC feasibility and reproducibility and (2) to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…We hypothesize that manual adjustment applied for improving the delineation of both ventricles, especially the RV, led to differences in the endocardial delineation, in particular variations of transverse diameters that compute for the SI and FS segmental analysis. In our study, we performed a manual adjustment of the semi-automatic tracking of both ventricles in most of our cases, especially for the RV, considering the endocardium and moderator band as part of the ventricular cavity [ 44 ]. Furthermore, SI and FS are calculated by a mathematical formula (SI: end-diastolic longitudinal diameter/end-diastolic transverse diameter, for each segment; FS: (end-diastolic transverse diameter-end-systolic transverse diameter)/end-diastolic transverse diameter, for each of the 24 segments), which may increase the error of both measures and explain the poorer reproducibility compared to other parameters that do not apply formulas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that manual adjustment applied for improving the delineation of both ventricles, especially the RV, led to differences in the endocardial delineation, in particular variations of transverse diameters that compute for the SI and FS segmental analysis. In our study, we performed a manual adjustment of the semi-automatic tracking of both ventricles in most of our cases, especially for the RV, considering the endocardium and moderator band as part of the ventricular cavity [ 44 ]. Furthermore, SI and FS are calculated by a mathematical formula (SI: end-diastolic longitudinal diameter/end-diastolic transverse diameter, for each segment; FS: (end-diastolic transverse diameter-end-systolic transverse diameter)/end-diastolic transverse diameter, for each of the 24 segments), which may increase the error of both measures and explain the poorer reproducibility compared to other parameters that do not apply formulas.…”
Section: Discussionmentioning
confidence: 99%
“…Endocardial border was tracked semi-automatically, obtaining a speckle-tracking algorithm, along the cardiac cycle ( Figure 2 ). End-diastolic endocardial tracking was then adjusted if necessary, especially the RV, so that the endocardium, the muscular trabeculations and the moderator band were considered the RV cavity [ 44 ]. Both ventricles were divided into 24 segments automatically [ 27 ] to allow analysis of the base (segments 1–8), mid ventricle (segments 9–16) and apex (segments 17–24).…”
Section: Methodsmentioning
confidence: 99%
“…We also demonstrated high feasibility and reproducibility for these measurements by 2D and M‐mode. These charts represent novel longitudinal charts constructed following current standardized landmarks to measure different cardiac morphometric and functional parameters 28–41 . Our group has previously demonstrated that uncomplicated MCDA twin fetuses present echocardiographic differences as a result of cardiac adaptation to volume/pressure overload when compared to singletons, 18 therefore, the use of our curves could help distinguish more accurately between adaptative or abnormal cardiovascular changes associated to MC pregnancy complications, optimizing the available therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…FAC was calculated as = [(end‐diastolic RV area−end‐systolic RV area)/end‐diastolic RV area] × 100 37 . Manual tracing of the RV area is explained in the cardiac dimensions section 37 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation